Brief Metacognitive Therapy for Emotional Distress in Adult Cancer Survivors - Fisher, Peter L.; Byrne, Angela; Fairburn, Louise; Ullmer, Helen; Abbey, Gareth; Salmon, Peter (Frontiers in Psychology, 2019)
ABSTRACT Background: Adult cancer survivors often experience substantial psychological morbidity following the completion of acute cancer treatment. Unfortunately, current psychological interventions are of limited efficacy. This study explored if metacognitive therapy (MCT); a brief transdiagnostic psychological intervention was potentially efficacious and could be delivered effectively to adult cancer survivors with psychological morbidity. Method: An open trial with 3- and 6-months follow-up evaluated the treatment effects of MCT in 27 consecutively referred individuals to a clinical psychology health service specialising in psycho-oncology. Each participant received a maximum of six 1-hour sessions of MCT. Levels of anxiety, depression, fear of cancer recurrence, post-traumatic stress symptoms, health related quality of life, and metacognitive beliefs and processes were assessed using self-report questionnaires. Results: MCT was associated with statistically significant reductions across all outcome measures which were maintained through to 6 months follow-up. In the ITT sample on the primary treatment outcome measure, the Hospital Anxiety and Depression Scale-Total, 59% of participants met recovery criteria at post treatment and 52% at 6 months follow-up, respectively No participants significantly deteriorated. In the completer sample (N=20), 80% recovered at post-treatment and 70% at 6 months follow-up. MCT was acceptable to patients with approximately 75% of patients completing all treatment sessions. Conclusion: MCT, a brief transdiagnostic psychological intervention can be delivered effectively to a heterogenous group of cancer survivors with promising treatment effects. Examining the efficacy of brief MCT against the current gold standard psychological intervention would be a valuable advance towards improving the quality of life of cancer survivors.